« Words are not simple play things! » : L’hétérolinguisme théâtral chez Louis Patrick Leroux - Nolette, Nicole (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This article explores how, in the 1990s, Canadian playwright Patrick Leroux broke away from previously prevalent representations of bilingualism in minority Franco-Ontarian drama and made multilingualism and translation into theatrical “play things”. His most playful performance text, Le Rêve totalitaire de dieu l’amibe, features as many games as issues at stake for staging experimental minority theatre. Substractive ideologies around bilingualism are torn apart, heterolingualism is raised and deconstructed like a strange tower of Babel and translation becomes BabelFish-like. L’ombre du lecteur anglais (The shadow of the English reader) and an Anglophone commentator are added to a production that is constantly reworked, retranslated and surtitled. The trajectory of the production from Ottawa to Sudbury (in Ontario) and Saint-Lambert (in Quebec), and then on to Montreal and to Hull, delineates a playground for translation riddled with layers of address to spectators, depending on their level of comprehension of the languages spoken on (and off) stage.